2009
DOI: 10.1111/j.1746-1561.2009.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Materials on Teacher Adoption of Abstinence‐Only‐ Until‐Marriage Programs

Abstract: Trends in political agendas, policy development, and state and federal funding have supported abstinence-only-until-marriage education programs. In order to ensure an understanding about the inclusion of sexuality education in the classroom, insight into the teacher's role in the integration of sexuality education in the classroom is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Results highlight the use of national standards in health and sexuality education as a guiding framework for making curricula decisions. Rarely are these decisions made based on one key topic area, therefore, understanding to what extent a curricula includes national, district, or school standards is important for review committees and adopters to consider …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results highlight the use of national standards in health and sexuality education as a guiding framework for making curricula decisions. Rarely are these decisions made based on one key topic area, therefore, understanding to what extent a curricula includes national, district, or school standards is important for review committees and adopters to consider …”
Section: Discussionmentioning
confidence: 99%
“…Among the curriculum, prices ranged from $0.00 for a free download and to $325.00 per copy; individual curricula ranged in price depending on if the purchaser was requesting a specific grade level or a downloadable copy versus print version. Acquisition information could be found online through developer websites …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they need to be able to assess students' relevant needs and assets, design activities that meet these needs, and deliver content consistent with community values. They must create a safe learning environment and foster student comfort in discussing sensitive topics 3–5…”
Section: Teacher Preparationmentioning
confidence: 99%
“…They must create a safe learning environment and foster student comfort in discussing sensitive topics. [3][4][5] When investigating teacher-preparation program requirements, Eisenberg, Madsen, Oliphant, Sieving, and Resnick 6 found that only 61% of colleges and universities require sexuality education courses for health education certification, and nearly one third of teachers responsible for sexuality education report receiving no pre-service or in-service training in this area. 6 In Pre-Service Teacher Training for School-Based Sexuality Educators: An Exploratory Study (unpublished data, 2013), Heitel, Ike, and Schroeder reported that little change has occurred: 57% of higher-education institutions with school health programs reported that they did not require sexuality courses, content, or teaching methodology for pre-service students.…”
Section: Teacher Preparationmentioning
confidence: 99%